CREATING A TRADITIONAL ORCHESTRA FOR THE NEEDS OF SPECIAL EDUCATION - Makris, Joannis (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The creation and teaching of a musical ensemble constitutes a complex process. The process becomes all the more complex when it entails the needs of Special Education. The goal of the present study is to present the teaching of a traditional orchestra to individuals suffering from intellectual deficits. Our methodological framework is anchored on: (a) Applied Behavior Analysis (Miller, 1962; Krumboltz & Krumboltz, 1972; Gibbs & Luyben, 1985; Kazdin, 1984) with the help of technology (Makris, 2015); and (b) the analysis of the mathematical law governing musical pleasure (Makris, Mullet, 2003). More specifically, we will be analyzing the manner in which we can create and teach a traditional orchestra to mentally disabled individuals through the application of the model “visual stimulus” – “psychophysical reaction”. The gradual shaping of behavior entails progressive reinforcement and not anticipation of perfection, the motive of the mentally disabled individuals to participate and be included. The results presented in the graphs confirm in practice the success of the present endeavor.